Anaerobic co-digestion of crude glycerin and starch industry effluent - Larsen,Andrea C. (2013)
The Brazil's Biodiesel Production and Use Program introduces biodiesel in the Brazilian energy matrix, bringing along the perspective of a growth of the glycerin offer, co-product generated in the proportion of 10 kg for each 100 L of biodiesel. The aim of this study was to evaluate the addition of crude glycerin in the anaerobic digestion of cassava starch industry effluent (cassava wastewater), in a horizontal semi-continuous flow reactor of one phase in laboratory scale. It was used a reactor with a 8.77 L of useful volume, a medium support for corrugated conduit of polyvinyl chloride (PVC), temperature of 261 ºC, fed with cassava wastewater and glycerin, with hydraulic detention times of 4 and 5 days and increasing volumetric organic load of 3.05; 9.32; 14.83 and 13.59 g COD L-1 d-1, obtained with the addition of glycerin at 0; 2; 3 and 2% (v/v), respectively. The average removal efficiencies of TS and TVS were decreasing from the addition of glycerin to the cassava wastewater, averaging 81.19 to 55.58% for TS and 90.21 to 61.45% for TVS. The addition of glycerin at 2% increased the biogas production compared to the control treatment, reaching 1.979 L L-1 d-1. The biogas production as a function of the consumed COD was higher for the control treatment than for the treatments with addition of glycerin, which indicates lower conversion of organic matter into biogas.